Enhancing Disaster Mitigation Understanding Through the Design of a Learning Module at SMA Negeri 3 Ambon - Rumengan, Marisa Enjely; Leuwol, Ferdinand Salomo; Tetelepta, Edward Gland (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Indonesia faces a high risk of natural disasters, making disaster mitigation education crucial. This study aims to evaluate the effectiveness of a geography-based learning module in enhancing students’ understanding of disaster mitigation at SMA Negeri 3 Ambon. A mix methods approach was employed, combining quantitative and qualitative methods. Data were collected through pretests, posttests, observations, and interviews. The results showed a 39.68% increase in average posttest scores, indicating improved student comprehension. Observations revealed that students became more engaged in discussions and simulations after using the learning module. Interviews with teachers highlighted that the module facilitated more systematic and practical delivery of materials. In conclusion, the geography-based learning module effectively enhances disaster mitigation understanding. However, further support in teacher training and curriculum refinement is needed to optimize its implementation